Pengaruh perubahan Tegangan dan frekuensi Sumber terhadap Efisiensi Motor Induksi Tiga Fase - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas MIPA Universitas Gadjah Mada, 2004)
ABSTRAK Generally induction motors are designed on certain input voltage and frequency that listed on the name plate. Improper voltage and frequency input affect induction motor performance which is not optimum. The objective of this research is to investigate the effect of the voltage and frequency on the efficiency of a three-phase induction motor. The research was done by changing the frequency source to find linear and quadratic portion of voltage and frequency supplied. The results of this research shows that by increasing frequency above the rating reduces the motor efficiency. For 200 W induction motor that works on 50 Hz frequency has efficiency 90 %. if frequency Keywords: tegangan frekuensi sumber, efisiensi motor